Interfacial-active polymer nanoparticles, their assemblies, and SERS application - Visaveliya, Nikunjkumar R.; Li, Xiang; Knauer, Andrea; Prasad, Bhagavatula L. V.; Kohler, Johann Michael (Macromolecular Chemistry and Physics, 2017)
In this work, surface-active polymer nanoparticles as well as polymer-polymer and polymer-metal nanoassembly particles are synthesized, and different parameters such as their size, morphologies, and assembling strength are studied. Nanoassembly particles are attractive because of the coupled properties with a large surface to volume ratio. A key challenge is to produce the core-shell polymer nanoparticles via single-step processes. To address this concern, here, microfluidics approach and precise interfacial reaction strategies are used, and hence different types of surface layered polymer nanoparticles are obtained in one-step processes. An inner core material is hydrophobic, whereas a hydrophilic surface layer (in situ formed during the polymerization process) swells in the aqueous environment. Moreover, three different reaction setups (batch, flow, and in situ) are applied in order to architect the nanoassembling hierarchical structures via layer-by-layer strategy. On the other side, polymer-metal nanoassembly particles as well as metal catalyzed metal deposited four layered nanoassembly particles of tuned size and compositions are produced. It is shown that these particles can be used as nanosensor particles for surface-enhanced Raman spectroscopy.